Medich Giant Platelet Syndrome: An Evolving Qualitative and Quantitative Platelet Disorder - Gita Massey; Laura Tyrrell; Yaser Diab; William T. Gunning (Hematology Reports, 2022)
Qualitative platelet disorders remain rare and varied. We describe here 2 additional patients with giant platelets, thrombocytopenia, deficiency in alpha granules and the presence of membranous inclusions within the cytoplasm. Collectively known as Medich syndrome, we further elucidated structural and clinical features of this rare syndrome. Platelets obtained from 2 patients with macro-thrombocytopenia were evaluated by electron microscopy. Structural findings were correlated with clinical characteristics. The defining morphologic feature found in the platelets of these patients is the presence of long, tubular inclusions consisting of several layers of membrane wrapped around a core of cytoplasm. These inclusions may deform the discoid shape of the platelet. In addition, abnormal giant alpha granules are present. Clinically all patients in the current report and review of the literature had mucosal bleeding and were often misdiagnosed as having immune related thrombocytopenia. To date five cases of Medich giant platelet syndrome have been reported. The cases are unified by the ultrastructural findings of abnormal alpha granules and unusual cytoplasmic scrolls. All patients experienced mucosal bleeding, however many clinical, biologic and genetic characteristics of this rare disorder remain to be determined.